Вплив надлишку та нестачі мелатоніну на продукцію супероксиду в тонкій кишці щурів - Анасевич, Ярослав; Anasevych, Jaroslav (Східноєвропейський національний університет імені Лесі Українки, 2015)
Нестача мелатоніну сприяє збільшенню продукції супероксиданіонрадикалу в тонкій кишці щурів від фагоцитарних електронно-транспортних ланцюгів, а надлишок – від мітохондріального окиснення, що відпо- відає антиоксидантним властивостям мелатоніну. Витік супероксиду з мікросомального електронно- транспортного ланцюга окиснення в обох випадках не змінювався. In the small intestine of rats lack of melatonin for 30 days (lighting 1000–1500 lux) increases production by phagocytic elektoronno superoksidanionradikal transport chains, and the excess of melatonin (the content of rats in the dark, and oral administration of melatonin in a daily dose of 1 mg / kg body weight) – from mitochondrial oxidation, which corresponds to the antioxidant capacity of melatonin. Emerging superoxide with microsomal electron transport chain oxidation in both cases did not change. When comparing the same for the term of the shortage and excess of melatonin it was found that the shortage of the relative weight of the small intestine is 1,8 times less than the excess. Almost twice the relative weight of the small intestine in a 30-day conditional lack of melatonin is less than normal. 10 % weight ratio of the small intestine with an excess of melatonin less conventional standards, can be estimated as a result of an imbalance of melatonin production.
Effect of Excess and Shortage of Melatonin on Superoxide Production in the Small Intestine of Rats
Keywords: гіпомелатонінемія; гіпермелатонінемія; тонкий кишечник; супероксиданіонрадикал; small intestine; superoxidanionradical; hipomelatoninnemia; hypermelatoninnemia